Beyond Borders: A Comparative Analysis of “Migrant” and “Refugee” Protections in International and EU Law - Wielec, Marcin (Migration and Central Europe: Challenges and Legal Responses, 2024)
This chapter presents a comparative analysis of the terms “refugee” and “migrant” and the forms of protection they are granted under international and European Union (EU) laws. The text also includes information and insights into the Serbian, Croatian, Slovenian, Romanian, Czech, Slovak, Hungarian, and Polish legal frameworks. First, the chapter begins with a concise introduction, outlining the general subject and scope of the study. Second, the manner in which globalisation is the basis for migration and refugees is analysed and presented. Third, the levels of regulation and types of legislation defining the migration and refugee processes were addressed. Fourth, a review of the EU legislation on migration, including asylum laws, is presented. Fifth, the legal stages of the migrant and refugee concepts were examined. Sixth, general considerations of the concepts of migrants and refugees are presented. Seventh, a legal and comparative account of migration and refugee terms is discussed. Eighth, definitions of migration and refugees in international and EU laws are presented. The focus on international and EU law should not be taken as an indication of the author’s position regarding the nature of EU law as either an autonomous branch or a part of international law; the distinction is made solely to aid in clarity. The chapter concludes with a concise summary of the overall conclusions, which are presented at 10 key points. Finally, the author’s main thesis on this topic is presented. Keywords: migrant, refugee, comparative analysis, international law, EU law.